The champion - Matharu, Taran (Matharu, Taran. Contender, 2021)
"In this explosive final book in the Contender trilogy, Cade and his friends wage the ultimate battle for their lives--and the fate of Earth itself--in the Game set by the cruel and mysterious Pantheon"--